2007
DOI: 10.1213/01.ane.0000287660.29297.7b
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of p38 Mitogen-Activated Protein Kinase Inhibitor on Synthesis of Inflammatory Cytokine Tumor Necrosis Factor Alpha in Spinal Cord of Rats with Chronic Constriction Injury

Abstract: p38 MAPK activation is one aspect of the signaling cascade that culminates in TNF-alpha synthesis and contributes to mechanical allodynia after peripheral nerve injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 25 publications
2
42
0
Order By: Relevance
“…Activated p38 in DRG and spinal cord was transiently elevated after SnL and then recovered to basal levels 25 . Xu 26 , Lee 28 and present data indicate that activated p38 in spinal cord elevated after CCI and sustained for 14 days and more. Differences among the various models seem to cause substantial differences in spinal p38 activation.…”
Section: Discussionsupporting
confidence: 64%
“…Activated p38 in DRG and spinal cord was transiently elevated after SnL and then recovered to basal levels 25 . Xu 26 , Lee 28 and present data indicate that activated p38 in spinal cord elevated after CCI and sustained for 14 days and more. Differences among the various models seem to cause substantial differences in spinal p38 activation.…”
Section: Discussionsupporting
confidence: 64%
“…Accumulating evidence shows that MAPKs mediate the production of a variety of proinflammatory cytokines and chemokines in glial cells (Gao et al, 2009;Lu et al, 2013;Xu et al, 2007). Our previous results showed that the protein expression of MCP-1 was regulated by JNK and ERK pathway in astrocytes (Gao et al, 2009).…”
Section: Ho-1 Induction Reduces Activation Of Mapks and Production Ofmentioning
confidence: 86%
“…7 Moreover, Ang-(1-7) binding to MasR may inhibit phosphorylation of p38 MAPK. 41 Phosphorylation of spinal p38 MAPK has been observed in chronic injury, 77 and therefore a decrease in phospho-p38 MAPK in chronic injury models such as CIBP may prove to yield antinociceptive effect. MasR activation by Ang-(1-7) can activate nitric oxide synthase, increasing intracellular NO 8 to further increase intracellular levels of cyclic GMP (cGMP).…”
Section: Discussionmentioning
confidence: 99%